The Role of Islamic Character Education in Developing Discipline in Schools: Peran Pendidikan Karakter Islami Dalam Pembinaan Kedisiplinan Di Sekolah - Hilmi, Fuad (CV. Media Publikasi Profesional, 2023)
Building discipline through Islamic character education does not just regulate external behavior, but also strengthens internal values and principles that encourage individuals towards strong discipline, high morality and complete responsibility. The aim of this research is to review the role of Islamic Character Education in fostering discipline at the Syahida Vocational High School (SMK). The research method used was descriptive qualitative with the selection of research subjects using purposive sampling. Data collection was carried out through observation, interviews, and documentation, with research subjects including school principals, student affairs staff, Islamic Religious Education teachers, and students. Data analysis is carried out through the stages of data collection, data reduction, data display and verification. The results of the research show that the development of discipline through Islamic character education at Syahida Vocational School is reflected in the high level of student discipline, which is reflected in various activities such as prayer before and after studying, celebrating religious holidays, and congregational prayers in the school environment. This success was verified through a data assessment rubric which included observation, interviews and documentation, showing that Islamic character education is able to form students who have discipline. From the results of this research, it can be concluded that fostering discipline through Islamic character education is very effective in forming students with noble and responsible morals.